17β hydroxysteroid dehydrogenase 3 deficiency in 46, XY disorders of sex development: Our experience and a gender role‐focused systematic review. (27th February 2022) - Krishnappa, Brijesh; Arya, Sneha; Lila, Anurag R.; Sarathi, Vijaya; Memon, Saba S.; Barnabas, Rohit; Kumbhar, Bajarang V.; Bhandare, Vishwambhar V.; Patil, Virendra; Shah, Nalini S.; Kunwar, Ambarish; Bandgar, Tushar
Abstract: Objectives: To describe Asian Indian patients with 17β hydroxysteroid dehydrogenase 3 (17βHSD3) deficiency and to perform a systematic review to determine the factors influencing gender role in 46, XY disorder of sex development (DSD) due to 17βHSD3 deficiency. Patients and Design: We present the phenotypic and genotypic data of 10 patients (9 probands and 1 affected family member) with 17βHSD3 deficiency from our 46, XY DSD cohort ( N  = 150; Western India) and a systematic review of 152 probands with genetically proven, index 17βHSD3 deficiency patients from the world literature to identify the determinants of gender role. Results: 17βHSD3 deficiency was the third most common (6%) cause of non‐dysgenetic 46, XY DSD in our cohort. Five patients each had prepubertal (atypical genitalia) and pubertal (primary amenorrhoea) presentations. Six patients were initially reared as female of whom two (one each in prepubertal and pubertal age) changed their gender role. Ten pathogenic molecular variants (six novel) were observed. In the systematic review, initial male sex of rearing was uncommon (10.5%) and was associated with atypical genitalia, higher testosterone/androstenedione (T/A) ratio and Asian origin. Gender role change to male was seen in 10.3% of patients with initial female sex of rearing and was associated with Asian origin but unrelated to pubertal androgens or molecular variant severity. It has not been reported in patients of European origin. Conclusions: We report the first Indian case series of 17βHSD3 deficiency, the third most common cause of 46, XY DSD, with six novel molecular variants. Distinct geographical differences in the frequency of initial male sex of rearing and gender role change to male in those initially reared as females in 17βHSD3 deficiency were noted which needs further evaluation for the underlying molecular mechanisms.